Anti-nucleosome antibodies as a disease activity marker in patients with systematic lupus erythematosus - Ha, Suliman Tayseer (2006)
The clinical aspect of measuring the level of anti-nucleosome antibodies in patients with systemic lupus erythematosus (SLE) has been well established and it is claimed that their presence is associated with the disease activity. The overall aim of this study was to measure the level of anti-nucleosome· antibodies in the SLE patients, to determine the sensitivity as well as the specificity of these antibodies in the diagnosis of the disease. The evaluation of the relationship between the levels of anti-nucleosome antibodies, the disease activity as well as and other markers (anti-dsDNA antibodies, C3, C4 and CRP) were also compared and assessed. In this cross sectional study, all patients were selected from Hospital Universiti Sains Malaysia (HUSM), who were either attending the medical specialist's clinic or have been admitted to the medical wards. Ninety SLE patients, forty-five other connective tissue diseases (e.g., rheumatoid arthritis, mixed connective tissue disease, scleroderma, Raynaud's syndrome and Sjogren's s~drome) and ninety normal controls were tested for anti-nucleosome antibodies by enzyme linked immunosorbent assay (ELISA), anti-dsDNA and ANA by Immunofluorescence (IF), C3, C4 and CRP by immunoturbidometry techniques. SLE diseases activity was evaluated by using SLE-Disease Activity Index (SLEDAI) score. A patient is defined as having active SLE when SLEDAI score is more than 5.0 Out of 90 SLE patients, anti-nucleosome antibodies were positive in 52% of patients, whereas these antibodies were positive in 7% of patients with other connective tissue diseases. The median concentration of anti-nucleosome antibodies was significantly different between SLE patients and other connective tissue diseases. None of the normal controls was found to be positive for these antibodies. Anti-dsDNA antibodies were positive in 3 7% SLE patients, whereas these antibodies were positive in 8% of patients with other connective tissue diseases. None of the normal controls was found to be positive for these antibodies. ANA was found to be positive in 81% SLE patients, in 61% of patients with other connective tissue diseases and 7% in normal controls. Anti-nucleosome antibodies had a sensitivity of 52%, whereas anti-dsDNA antibodies had a sensitivity of 37%. The specificity of anti-nucleosome and anti-dsDNA antibodies was 98% and 97% respectively. ANA had sensitivity and specificity of 81% and 75% respectively. Antinucleosome antibodies were positive in 98% of patients with active SLE, whereas these antibodies were positive in 14% of patients with inactive SLE. The median concentration of anti-nucleosome antibodies was significantly different between active and inactive SLE patients. Anti-dsDNA antibodies were found to be positive in 61% of patients with active SLE and in 16% of patients with inactive SLE. Anti-nucleosome antibodies had a stronger correlation than anti-dsDNA antibodies with SLEDAI score. The median concentration of C3 and C4 was significantly different between active and inactive SLE patients, and showed an inverse and significant correlation with SLEDAI score, whereas the median concentration of CRP was not significantly different between active and inactive SLE. In conclusion, anti-nucleosome antibodies test is a recently developed test that may help in diagnosis of SLE patients. Anti-nucleosome antibodies are highly sensitive and specific for the diagnosis of SLE, especially when the anti-dsDNA antibodies are absent. Thus antinucleosome antibodies test can be a better tool for the diagnosis of SLE. Anti-nucleosome antibodies have a stronger and significant correlation with SLEDAI score than other traditional disease activity markers. Therefore, it can be a useful and additional disease activity marker to other laboratory tests that can help in the assessment SLE disease activity.